2011
DOI: 10.1590/s1679-45082011ao1897
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload in Brazilian thalassemic patients

Abstract: A high rate of hepatic, pancreatic and cardiac impairment by iron overload was demonstrated. Ferritin levels could not predict liver, heart or pancreas iron overload as measured by T2* magnetic resonance imaging. There was no correlation between liver, pancreas, liver and myocardial iron overload, neither between ferritin and fraction of labile plasma iron with liver, heart and pancreas T2* values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…This is explained by the fact that both pancreas and cardiac iron overload share the same iron loading pathway. This finding is similar to other study findings (14,17,18,20,21). One large multicentric observational study indicated that pancreatic iron is a powerful predictor of not only glucose metabolic dysfunction but also the cardiac iron and its complication (22).…”
Section: Figuresupporting
confidence: 94%
“…This is explained by the fact that both pancreas and cardiac iron overload share the same iron loading pathway. This finding is similar to other study findings (14,17,18,20,21). One large multicentric observational study indicated that pancreatic iron is a powerful predictor of not only glucose metabolic dysfunction but also the cardiac iron and its complication (22).…”
Section: Figuresupporting
confidence: 94%
“…These variable results could be because of differences in clinical, genetic, and demographic characteristics of study population such as age, sample size, serum ferritin levels, chelating protocols, and iron kinetics of different organs. Our study population was more homogenous with narrow age range (2–18 years) in comparison to previous studies[ 19 20 22 23 ] where age group ranged from as young as 5 years to as old as 54 years. Overall, our population was also quite younger than previous studies; mean age - 9.06 ± 4.64 years in our study versus 22.79 ± 7.1 and 22.77 ± 6.2 thalassemia major and intermedia groups, respectively, in Majd et al .,[ 16 ]21.25 years in Assis et al .,[ 23 ] 24.1 ± 5.4 years in Azarkeivan et al .,[ 19 ] and 25.59 ± 8.5 years in Zamani et al .…”
Section: Discussionmentioning
confidence: 65%
“…[ 22 ] showed moderate correlation, and in contrast to our study, Assis et al . [ 23 ] demonstrated excellent correlation between serum ferritin and T2* MRI liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations